IMPLEMENTASI KEWIRAUSAHAAN SYARIAH SANTRI DI SEKOLAH MENENGAH KEJURUAN PONDOK PESANTREN MODERN SAHID MARYAM AFIFAH - Maryam Afifah (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2023)
This study aims to find out how Santi entrepreneurship is implemented at Sahid Vocational School and how to instill Islamic values in entrepreneurship practices at Sahid Vocational School. This study uses a qualitative method with a field research approach which is presented descriptively. Data collection in this study was carried out by means of interviews, observation, and documentation of 10 informants consisting of 5 Sahid Vocational School administrators and 5 Santri. The results of the study show that the entrepreneurship of students applied at SMK Pondok Pesantren Sahid Modern aims to foster an entrepreneurial spirit, independent spirit, and prepare students to take advantage of every business opportunity by creating entrepreneurial products and selling them at school events, such as school festivals. , acceptance of new students, or other activities. Products produced by SMK Sahid students include culinary products such as market snacks, continental and oriental dishes as well as long-lasting packaged dishes such as pastries and chips. In instilling Islamic values in entrepreneurship practices at SMK Pondok Pesantren Modern Sahid, halal raw materials and the values of honesty and trust are important and must be prioritized in every activity, including entrepreneurial activity. In harmony with what was taught and exemplified by the Prophet Muhammad SAW